Structural and Biological Assessment of Zinc Doped Hydroxyapatite Nanoparticles. (30th June 2016) - Popa, Cristina Liana; Deniaud, Aurélien; Michaud-Soret, Isabelle; Guégan, Régis; Motelica-Heino, Mikael; Predoi, Daniela
Abstract : The aim of the current research work was to study the physicochemical and biological properties of synthesized zinc doped hydroxyapatite (ZnHAp) nanoparticles with Zn concentrationsx Zn = 0 (HAp), x Zn = 0.07 (7ZnHAp), andx Zn = 0.1 (10ZnHAp) for potential use in biological applications. The morphology, size, compositions, and incorporation of zinc into hydroxyapatite were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier Transform Infrared Spectroscopy (FTIR), Raman scattering, and X-Ray Photoelectron Spectroscopy (XPS). In addition, the cytotoxicity of ZnHAp nanoparticles was tested on both E. coli bacteria and human hepatocarcinoma cell line HepG2. The results showed that ZnHAp nanoparticles (HAp, 7ZnHAp, and 10ZnHAp) have slightly elongated morphologies with average diameters between 25 nm and 18 nm. On the other hand, a uniform and homogeneous distribution of the constituent elements (calcium, phosphorus, zinc, and oxygen) in the ZnHAp powder was noticed. Besides, FTIR and Raman analyses confirmed the proper hydroxyapatite structure of the synthesized ZnHAp nanoparticles with the signature of phosphate, carbonate, and hydroxyl groups. Moreover, it can be concluded that Zn doping at the tested concentrations is not inducing a specific prokaryote or eukaryote toxicity in HAp compounds.